The Usage of Interactive Teaching Methods in L2 Classroom to Enhance Future Philologists’ Subjectness - ARISTOVA, NATALIIA (Journal of Education, Technology and Computer Science, 2017)
The author discusses the problem of eliciting and implementing interactive teaching methods in L2 classroom to enhance future philologists’ subjectness. The necessity to use interactive teaching methods such as educational discussion, didactic games, debates, ‘workshop’ method, partial-ly-inquisitive and research methods is theoretically grounded in the article.